Numerical Method on Blood Flow Pressure Drop in Aorta Coronary Sinus Conduit - Hussain, Siti Aslina; Tan, Hong Tat; Hamid, Mohd Ismail; Abdullah, Norhafizah; Idris, Azni (2010)
Numerical studies of blood flow system of aorta coronary sinus conduit were carried out using ANSYS™ CFD simulation. Pressure drop was investigated to achieve from 80 mmHg to 15 mmHg with a 3D model blood conduit. From the analysis of coronary sinus conduit, it is found that a narrow tube needs to be incorporated into the conduit produced. This is to induce a venturi effect to reduce the pressure of blood within a specific throat length. As a conclusion, a model of 3 mm inlet and throat diameter of 1.13 mm show satisfactory result for pressure reduction from 80 mmHg to 15 mmHg.